2022
DOI: 10.1002/nop2.1551
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement in postoperative pain management among children in a urology ward: A best practice implementation project

Abstract: Aim Postoperative pain has adverse effects on children with urological problems, including sleep disturbances, incision dehiscence, bleeding and delayed recovery. Accurate parental assessment of children's behaviours and responses could help to manage postoperative pain. We aimed to implement evidence‐based practice for parental involvement in a urology ward, to increase parents' participation in children's postoperative pain management. Design The project was conducted in a paediatric urology ward using the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…As such, non-pharmacological pain management strategies may be suggested as they are known to be applicable for patients in all age groups and are effective in relieving pain, with and without additional pharmacological intervention [12,[22][23][24][25]. Our findings were congruent with a best practice implementation project in that postoperative pain management practices remain suboptimal and non-pharmacological methods were not used as there was a lack of education provided to parents [3]. Pain medications are currently the primary strategy used in the hospital setting to control children's pain, and nurses in Singapore do not commonly apply non-pharmacological methods.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…As such, non-pharmacological pain management strategies may be suggested as they are known to be applicable for patients in all age groups and are effective in relieving pain, with and without additional pharmacological intervention [12,[22][23][24][25]. Our findings were congruent with a best practice implementation project in that postoperative pain management practices remain suboptimal and non-pharmacological methods were not used as there was a lack of education provided to parents [3]. Pain medications are currently the primary strategy used in the hospital setting to control children's pain, and nurses in Singapore do not commonly apply non-pharmacological methods.…”
Section: Discussionsupporting
confidence: 68%
“…Pain medications are currently the primary strategy used in the hospital setting to control children's pain, and nurses in Singapore do not commonly apply non-pharmacological methods. The inadequacy in adopting non-pharmacological pain relief methods may be attributed to the nurses' concerns about an anticipated increase in workload or their lack of knowledge and expertise on these strategies [3,26] 3. Valizadeh et al [27] also suggested that some nurses might lack sensitivity and awareness of patients' pain management needs, which diminishes their application of these non-pharmacological methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children are thought to lack the capacity to comprehensively deliver the severity of their pain, causing most pain to be left untreated in almost half of the postoperative pediatric patients ( 9 ). According to Yang ( 82 ), as primary caregivers, the parents can deliver a better assessment of their child's pain to medical staff, thus improving the quality of pain management and building trust-based relationships between them. The evidence suggests reduced physical and emotional distress once parents can participate in managing physical care after their child ( 83 ).…”
Section: Resultsmentioning
confidence: 99%